2014
DOI: 10.1038/bjc.2014.47
|View full text |Cite
|
Sign up to set email alerts
|

High FoxP3 expression in tumour cells predicts better survival in gastric cancer and its role in tumour microenvironment

Abstract: Background:Forkhead Box P3 (FoxP3) is thought to be a key transcription factor in regulatory T cells (Tregs), and recent data indicate that it is expressed in several tumour cells. However, its precise roles in gastric cancer (GC) and the underlying mechanisms regulating the interaction between GC cells and lymphocytes remain unclear.Methods:FoxP3 expression was examined in tumour cells and Tregs in 150 cases of gastric precancer and cancer, and their prognostic significances were evaluated, respectively, usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
49
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(57 citation statements)
references
References 38 publications
6
49
1
1
Order By: Relevance
“…We previously showed that gastric cancer cells express IL-10 and that serum IL-10 concentrations tend to be higher in gastric cancer patients than in normal controls [39,40]. Furthermore, the number of Treg cells, the main source of IL-10, was found to be increased in blood and tumor tissue of gastric cancer patients [41]. We therefore postulate that the increase we observed in IgG4-positive cells in gastric cancer tissue is associated with IL-10 expression.…”
Section: Discussionsupporting
confidence: 51%
“…We previously showed that gastric cancer cells express IL-10 and that serum IL-10 concentrations tend to be higher in gastric cancer patients than in normal controls [39,40]. Furthermore, the number of Treg cells, the main source of IL-10, was found to be increased in blood and tumor tissue of gastric cancer patients [41]. We therefore postulate that the increase we observed in IgG4-positive cells in gastric cancer tissue is associated with IL-10 expression.…”
Section: Discussionsupporting
confidence: 51%
“…This result, which is based on the expression of our 32-gene signature, is also in line with previous clinical findings pertaining to the CD8+ T cell to Treg ratio in the tumor microenvironment [38,44]. Furthermore, we observed that FOXP3 expression was significantly elevated in the clinically favorable cluster of patient tumor samples (cluster1, P < 5.41e-14; data not shown), which is also in accord with previous FOXP3 related studies [45][46][47][48][49].…”
Section: Discussionsupporting
confidence: 93%
“…Through enumeration of CD8 + T cells of the IM, we found that the CD8 + T cell number on the tumor side had a greater effect on OS than that on the stromal side (P = 0.01, Figure 3, A and B + OSCC, and gastric cancer (34,35). Based on a positive correlation between an increased number of Tregs and the CD8 + T cell infiltrate (Figure 4), we posited that Tregs recruited to the TME might not be close enough to the CD8 + T cells to suppress their effector function.…”
Section: Density Of Cd8mentioning
confidence: 96%